Effect of team training on improving MRI study completion rates and no‐show rates. Issue 4 (6th April 2016) - Norbash, Alexander; Yucel, Kent; Yuh, William; Doros, Gheorghe; Ajam, Amna; Lang, Elvira; Pauker, Stephen; Mayr, Nina
Abstract : Purpose: Magnetic resonance imaging (MRI) is a high‐cost imaging modality, and an optimized encounter ideally provides high‐quality care, patient satisfaction, and capacity utilization. Our purpose was to assess the effectiveness of team training and its impact on patient show‐up and completion rates for their MRI examinations. Materials and Methods: A total of 97, 712 patient visits from three tertiary academic medical centers over 1‐year intervals were evaluated, totaling 49, 733 visits at baseline and 47, 979 after training. Each center's MRI team received team training skill training including advanced communication and team training techniques training. This training included onsite instruction including case simulation with scenarios requiring appropriate behavioral and communicative interventions. Orientation and training also utilized customized online tools and proctoring. The study completion rate and patient show‐up rate during consecutive year‐long intervals before and after team training were compared to assess its effectiveness. Two‐sided chi‐square tests for proportions using were applied at a 0.05 significance level. Results: Despite differing no‐show rates (5–22.2%) and study incompletion rates (0.7–3.7%) at the three academic centers, the combined patients' data showed significant ( P < 0.0001) improvement in the patients' no‐show rates (combined decreases from 11.2% to 8.7%) and incompletion rates (combined decreases from 2.3% to 1.4%). Conclusion: Our preliminary results suggest training of the imaging team can improve the no‐show and incompletion rates of the MRI service, positively affecting throughput and utilization. Team training can be readily implemented and may help address the needs of the current cost‐conscious and consumer‐sensitive healthcare environment. J. MAGN. RESON. IMAGING 2016;44:1040–1047.